2012
DOI: 10.1017/aee.2013.1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Sustainability Initiatives Across a Region: An Innovative Survey Approach

Abstract: The project of mapping sustainability initiatives across a region is part of a larger program of research about place and sustainability education for the Anthropocene, the new geological age of human-induced planetary changes (Zalasiewicz, Williams, Steffen, & Crutzen, 2010). The study investigated the location, nature and type of sustainability initiatives in the Gippsland region of Victoria, Australia. The purpose of the study was to trial the development of a place-based survey questionnaire to map initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In contrast to earlier research that identified Gippsland schools as deficient in EfS compared to the Victorian metropolitan areas (DEECD, 2007), the SSE validated EfS as a popular endeavour that is commonly integrated through science, the arts, maths, geography and history disciplines. Subseqent research that mapped the pedagogical approaches to sustainability in the region highlights sustainability as practiced through school–community partnerships involving local shires, volunteers and council-based sustainability officers that are integral to the longevity and effectiveness of EfS in primary schools (Green and Somerville, 2015; Somerville and Green, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to earlier research that identified Gippsland schools as deficient in EfS compared to the Victorian metropolitan areas (DEECD, 2007), the SSE validated EfS as a popular endeavour that is commonly integrated through science, the arts, maths, geography and history disciplines. Subseqent research that mapped the pedagogical approaches to sustainability in the region highlights sustainability as practiced through school–community partnerships involving local shires, volunteers and council-based sustainability officers that are integral to the longevity and effectiveness of EfS in primary schools (Green and Somerville, 2015; Somerville and Green, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The schools selected for Year 3 were self-identified in a previous research study 'Mapping sustainability initiatives in the Gippsland region' (Somerville and Green 2013). The aim of the parallel mapping study was to understand how to connect individual local sustainability initiatives to each other across a region in order to gain greater momentum for transformational change.…”
Section: Introductionmentioning
confidence: 99%
“…This project builds upon a number of Australian studies in rural education and sustainability that use the concepts of space and place to arrive at new understandings of existence and educational, social, cultural and environmental concerns which are often intractable (Cormack, Green, & Reid, 2006;Green, 2012;Somerville & Green, 2012;Vanclay, Higgins, & Blackshaw, 2008). This education research literature shares links with recent policy and governance studies on the idea of localism.…”
Section: The Approachmentioning
confidence: 99%